Morphological divergence and flow‐induced phenotypic plasticity in a native fish from anthropogenically altered stream habitats. Issue 14 (25th October 2013) - Franssen, Nathan R.; Stewart, Laura K.; Schaefer, Jacob F.
Abstract Understanding population‐level responses to human‐induced changes to habitats can elucidate the evolutionary consequences of rapid habitat alteration. Reservoirs constructed on streams expose stream fishes to novel selective pressures in these habitats. Assessing the drivers of trait divergence facilitated by these habitats will help identify evolutionary and ecological consequences of reservoir habitats. We tested for morphological divergence in a stream fish that occupies both stream and reservoir habitats. To assess contributions of genetic‐level differences and phenotypic plasticity induced by flow variation, we spawned and reared individuals from both habitats types in flow and no flow conditions. Body shape significantly and consistently diverged in reservoir habitats compared with streams; individuals from reservoirs were shallower bodied with smaller heads compared with individuals from streams. Significant population‐level differences in morphology persisted in offspring but morphological variation compared with field‐collected individuals was limited to the head region. Populations demonstrated dissimilar flow‐induced phenotypic plasticity when reared under flow, but phenotypic plasticity in response to flow variation was an unlikely explanation for observed phenotypic divergence in the field. Our results, together with previous investigations, suggest the environmental conditions currently thought to drive morphological change in reservoirs (i.e., predation and flow regimes) may not be the sole drivers of phenotypic change.